2022
DOI: 10.1002/dev.22271
|View full text |Cite
|
Sign up to set email alerts
|

Aperiodic electrophysiological activity in preterm infants is linked to subsequent autism risk

Abstract: Approximately 7% of preterm infants receive an autism spectrum disorder (ASD) diagnosis. Yet, there is a significant gap in the literature in identifying prospective markers of neurodevelopmental risk in preterm infants. The present study examined two electroencephalography (EEG) parameters during infancy, absolute EEG power and aperiodic activity of the power spectral density (PSD) slope, in association with subsequent autism risk and cognitive ability in a diverse cohort of children born preterm in South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 101 publications
1
30
0
Order By: Relevance
“…Thus, a wider range of frequencies in the parametrization of the aperiodic components affects the curve slope trajectory to fit higher frequencies. Indeed, the study of Shuffrey and colleagues (2022) found that the exponent between the 1 to 20 Hz range was larger than the exponent of the 21 to 40 Hz range in new-borns, which signals a steeper reduction of the aperiodic curve in the lower frequencies, which might be related to the presence of noise. Therefore, dividing the curve into low-frequency and high-frequency or computing the aperiodic parameters with a knee would be probably beneficial for the fit of the aperiodic background curve in infants.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, a wider range of frequencies in the parametrization of the aperiodic components affects the curve slope trajectory to fit higher frequencies. Indeed, the study of Shuffrey and colleagues (2022) found that the exponent between the 1 to 20 Hz range was larger than the exponent of the 21 to 40 Hz range in new-borns, which signals a steeper reduction of the aperiodic curve in the lower frequencies, which might be related to the presence of noise. Therefore, dividing the curve into low-frequency and high-frequency or computing the aperiodic parameters with a knee would be probably beneficial for the fit of the aperiodic background curve in infants.…”
Section: Discussionmentioning
confidence: 97%
“…In infant studies, authors have employed a narrower range of frequencies to compute the aperiodic parameters. For instance, Schaworonkow and Voytek (2021) analyzed the 1 to 10 Hz range, and Shuffrey and colleagues (2022) divided the range into 1 to 20 Hz and 21 to 41 Hz. These changes might affect the aperiodic curve, especially in infants with more motor artifacts that affect beta and gamma, frequency bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that neural power spectra exhibit rapid event-related changes in both oscillatory and aperiodic features, simultaneously. That is, rather than a pure oscillatory "spectral fingerprints" model (Fig 1A This phenomenon occurs in conjunction with a decrease in band-limited, oscillatory power in the alpha/beta band (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These results show that consideration of both periodic and aperiodic spectral features is essential to our understanding of the neural correlates of memory.…”
mentioning
confidence: 78%
“…While nascent, there is strong evidence that traditional analysis approaches conflate oscillations and aperiodic activity [10][11][12]. This likely has far-reaching implications as aperiodic activity has been shown to vary across cortical depth [13], change during development [14][15][16][17], and aging [18][19][20], shift between task states [21], and is altered in disease [22][23][24][25]. In particular, the power spectrum slope-or the "spectral tilt"-reflects a global aperiodic neuronal process that is modulated during visual processing [26,27] and working memory [10,28], and is implicated in memory consolidation [29].…”
Section: Introductionmentioning
confidence: 99%